RESEARCH ON VIBRATION CHARACTERISTICS OF LINEAR CONJUGATE PLANETARY GEAR REDUCER WITH SMALL TOOTH DIFFERENCE (MT) - CUI JianKun; XIA Juan; ZHOU KongTao (Jixie qiangdu)
Combining the linear conjugate tooth profile with the planetary gear transmission with small tooth difference, taking the linear conjugate small tooth difference planetary gear reducer as the research object, the structure natural frequency and vibration mode of the reducer are obtained through finite element modal analysis, which shows the reducer has good structural dynamic characteristics; through the simulation analysis of vibration characteristics, the vibration law of the reducer under typical working conditions is obtained, and the vibration test experiment is carried out. The vibration experiment results are consistent with the simulation results. The vibration characteristics research results show that the input speed has a significant impact on the vibration amplitude and frequency of the linear conjugate small tooth difference planetary gear reducer.